The use of GPS for continuous measurement of kinematic data and for the validation of a model in alpine skiing - Seifriz, F.; Mester, J.; Krämer, A.; Roth, R. (International Journal of Computer Science in Sport, 2002)
At the Institute for Theory and Practice of Training and Movement, a model was developed to calculate the running time and the optimal trajectory in alpine skiing applying genetic algorithms. A GPS-System offers new possibilities for measuring kinematic data of alpine skiers and could be used to validate the model of alpine skiing. The advantage of this GPS-System is the direct use of the results without time-consuming calculations. Further, the data of the GPS-System could be used to produce virtual camera rides and to evaluate the results under competition conditions and with regard to safety aspects (e.g. comparison between real and optimised trajectories, analysis of the curve radius, the angle of gate entrance and the centrifugal force). The aim of the study was to validate the practical use of this GPS-System in alpine skiing. The investigation showed that it is possible to record the kinematic data of a skier using a GPS-System to an accuracy of a few centimetres. Further, it is necessary to develop a smaller antenna with differential phase correction, thus enabling this to be fixed directly onto the ski so reducing errors in measured data and real trajectory.